The Correlation of Inflammatory Markers with Clinical Manifestation, Peritumoral Edema, and Recurrence in Meningioma Patients - Aninditha, Tiara; Auliya, Putri; Mulyadi, Rahmad; Aman, Renindra Ananda; Andriani, Rini; Sofyan, Henry Riyanto (http://dharmais.co.id/, 2025)
Background: Meningiomas can induce inflammation in their tumorigenesis process, thereby linking inflammation with clinical symptoms, peritumoral edema, and recurrence of meningiomas. Easily accessible and cost-effective inflammatory markers include the neutrophillymphocyte ratio (NLR) and monocyte-lymphocyte ratio (MLR). This study aims to investigate the relationship between peripheral inflammation markers, specifically the NLR and MLR, and their association with clinical symptoms, peritumoral edema, and meningioma recurrence.Method: A retrospective cohort study was conducted at Cipto Mangunkusumo National General Hospital from January 2016 to December 2019, utilizing a consecutive non-probability sampling method. Inclusion criteria were patients aged 18 years or older with meningiomas(gradesI-III), first surgery. Peripheral inflammatory markers were derived from differential blood counts, peritumoral edema data from radiological reports, and other data from medical records. The cut-off valuesfor NLR and MLR were determined to be 2.415 and 0.295, respectively. Bivariate analyses using ChiSquare and Mann-Whitney tests were followed by multivariate logistic regression analysis. Results: 173 patients were eligible for analysis. Of these, 27 had preoperative CT scans, 126 had MRIs, and 20 had no preoperative radiology data. Clinical and recurrence analyses were performed on all 173 patients, with radiology and tumor size analyses conducted on subsets of 153 and 126 patients, respectively. The majority of meningiomasin thisstudy were grade I, found in 94.2% of subjects, with the remainder being grade II and III. Higher NLR and MLR values were significantly associated with headaches (p 0.001). Elevated NLR and MLR were also correlated with peritumoral edema (p 0.001). MLR was independently associated with recurrence, with an adjusted odds ratio (aOR) of 12.647 (95% CI 2.355–67.919); p = 0.003.Conclusion: NLR and MLR as peripheral inflammatory markers demonstrated higher median values in meningioma patients with headaches and peritumoral edema. Additionally, inflammation in meningiomas was associated with the occurrence of recurrence.